Osteosarcoma and Metastasis - Sheng, Gaohong; Gao, Yuan; Yang, Yong; Wu, Hua (Frontiers in Oncology, 2021)
Osteosarcoma is the most common primary bone malignancy in adolescents. Its high propensity to metastasize is the leading cause for treatment failure and poor prognosis. Although the research of osteosarcoma has greatly expanded in the past decades, the knowledge and new therapy strategies targeting metastatic progression remain sparse. There is resonating urgency for a thorough and deeper understanding of molecular mechanisms underlying osteosarcoma to develop innovative therapeutics targeting metastasis. Toward the goal of elaborating the fundamental characteristics and biological behavior of metastatic osteosarcoma, it is essential to combine the diverse investigations that are performed at molecular, cellular and animal levels from basic research to clinical translation spanning chemical, physical sciences and biology. This review focuses on the metastatic process, regulatory networks involving key molecules and signaling pathways, the role of microenvironment, osteoclast, angiogenesis, metabolism, immunity and noncoding RNAs in osteosarcoma metastasis. The aim of this review is to provide an overview of current research advances, with the hope to discovery druggable targets and promising therapy strategies for metastasis and thus to overcome this clinical impasse.